Recent changes in climate and permafrost temperatures at forested and polar desert sites in northern Canada 1 This article is one of a series of papers published in this CJES Special Issue on the theme of Fundamental and applied research on permafrost in Canada. - Smith, Sharon L.; Throop, Jennifer; Lewkowicz, Antoni G. (Canadian Journal of Earth Sciences, 2012)
Climate and ground temperature records up to 30 years in length from permafrost monitoring sites in a polar desert at Alert, Nunavut, and a boreal forest at Table Mountain, Northwest Territories, were analyzed by season and year to assess the ground thermal response to recent climate warming. Methods were developed to standardize incomplete ground temperature data sets and to hindcast air temperatures for comparative analysis. The timing and magnitude of climate warming varied, beginning in the 1960s in the Mackenzie Valley and the 1970s in the High Arctic. Ground temperature increases occurred in both regions but varied in magnitude and timing in relation to the external forcing and permafrost conditions. Significant increases in winter air temperatures in both regions appear to be largely responsible for recent increases in ground temperature, particularly at the polar desert sites where snow cover is minimal.